Identification of Endocrine-Disrupting Compounds Using Nanoelectrospray Ionization Mass Spectrometry - Cédric Bovet; Marc Ruff; Arno Wortmann; Sylvia Eiler; Florence Granger; Bertran Gerrits; Dino Moras; Renato Zenobi (CHIMIA, 2008)
A method using chip-based nanoelectrospray mass spectrometry (nanoESI-MS) is described to detect noncovalent ligand binding to the human estrogen receptor alpha ligand-binding domain (hER? LBD). This system represents an important environmental interest, because a wide variety of molecules, known as endocrine-disrupting compounds (EDCs), can bind to the estrogen receptor (ER) and induce adverse health effects in wildlife and humans. An efficient analytical method is therefore required to identify EDCs and characterize their solution-phase binding affinity and character (i.e. agonist or antagonist). Using proper experimental conditions, the nanoESI-MS approach allowed the detection of specific ligand interactions with hER? LBD. The best approach to evaluate solution-binding affinity by nanoESI-MS was to perform competitive binding experiments with 17?-estradiol (E2) as a reference ligand. Among the ligands tested, the relative binding affinity for hER? LBD measured by nanoESI-MS was 4-hydroxytamoxifen ? diethylstilbestrol > E2 ? genistein ? bisphenol A, consistent with the order of the binding affinities in solution. To discern agonist from antagonist, we used the specificity of a coactivator peptide for agonist-bound receptor. A specific coactivator-hER? LBD complex was detected only in the presence of an agonist ligand. Therefore, the specificity of nanoESI-MS combined with its speed (1 min/ligand), low sample consumption (90 pmol protein/ligand), and its sensitivity for ligand (30 ng/ml) demonstrates that this method is promising for the identification and characterization of suspected ER ligands in a high-throughput manner.